An exploration of tutor and provider perspectives of tutor CPD in the private FET sector in Ireland - Doran, Elizabeth (Trinity College (Dublin, Ireland). School of Education, 2022)
This study focuses on the gap in literature and research on tutor CPD in the private Further Education and Training (FET) sector in Ireland. The study explores a) FET tutor’s perspectives and experiences of their own learning and continuous development, b) private providers’ attitudes to CPD of their independent tutors, and c) the perspectives of both towards CPD accountability and increased professionalism. A mixed method approach which is quantitative and qualitative in nature within the interpretivist paradigm was employed to answer the research questions. Phase 1 used an online survey to both providers and tutors to investigate the differences in opinion on tutor entry requirements, professionalism, and CPD. It also examined the commitment of both towards CPD and its accountability. Phase 2 consisted of 4 provider interviews and 4 tutor interviews. Thematic analysis was used to determine the key themes and sub themes which included provider culture/size and provider/tutor responsibility to learners. It was determined from the study that individual tutor characteristics and industry experience can be given preference by providers over pedagogical qualifications and that tutor requirements can vary but are provider led. Both parties agreed that each had responsibly for CPD but ultimately the tutors themselves were accountable. Provider policy on staff development is not seen in practice with an absence of formal CPD plans in place for independent tutors. The ad hoc CPD undertake is driven by tutors’ responsibility to their learners to stay relevant and up to date, and by the providers perceived compliance with QQI Quality Assurance agreements, which is also influenced by their size and culture. A CPD framework which would recognise tutors’ competencies and experience was welcomed by both parties, both in agreement that this responsibility should lie with QQI. This study contributes to relevant literature where research on the private sector is limited. While the focus on recent policy on CPD in the public sector, in combination with QQI guidelines has created more awareness on CPD, policy makers and regulators need to be more inclusive of the private sector in policy development and strategic planning while providers also play a main role.
Keywords: Leadership and Management; Education